2004
DOI: 10.1242/jeb.00758
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive function of soil consumption: anin vitrostudy modeling the human stomach and small intestine

Abstract: Despite occurring in a wide variety of taxa, deliberate soil consumption (geophagy) is a poorly understood behavior. In humans, geophagy is sometimes considered aberrant or a sign of metabolic dysfunction. However, geophagy is normally assigned an adaptive function in nonhuman primates and various other organisms. One hypothesis submits that clay-rich soil adsorbs intestinal insults, namely plant metabolites or diarrhoea-causing enterotoxins. Here we test the capacity of kaolin, a commonly ingested clay, to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 63 publications
1
83
0
3
Order By: Relevance
“…They can firmly and selectively bind harmful substances from feeds in the intestines and thus reduce their absorption across the intestinal mucosa and resulting toxic effect (Knezevic and Tadic, 1994;Phillips, 1999;Abdel-Wahhab et al, 1999;Hassen et al, 2003;Katsumata et al, 2003;Dominy et al, 2004). Bartko et al (1983) and Boranic (2000) emphasized the high selective ion exchange capacity of clay minerals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They can firmly and selectively bind harmful substances from feeds in the intestines and thus reduce their absorption across the intestinal mucosa and resulting toxic effect (Knezevic and Tadic, 1994;Phillips, 1999;Abdel-Wahhab et al, 1999;Hassen et al, 2003;Katsumata et al, 2003;Dominy et al, 2004). Bartko et al (1983) and Boranic (2000) emphasized the high selective ion exchange capacity of clay minerals.…”
Section: Discussionmentioning
confidence: 99%
“…Natural clay minerals improve the function of the intestinal barrier and are effective in treating gastroenteric diseases in humans and animals (Castro and Elias, 1978;Said et al, 1980;Vrzgula et al, 1982;Brouillard and Rateau, 1989;Ramu et al, 1997;Narkeviciute et al, 2002;Dominy et al, 2004;Castro, 2005). Their use retards the rate of digestive passage through the intestines and their ability to absorb water results in more compact and better shaped faeces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clay, given to the animals in the diet, firmly and selectively binds compounds present in the diets which are noxious to the intestine and thus decreases their absorption through intestinal mucosa into the organism and subsequently prevents their toxic mode of action (Phillips, 1999). A number of studies confirmed clay capability to decontaminate aflatoxins (Abdel-Wahhab et al, 1999) plant metabolites (alkaloids, tannins), diarrhea causing enterotoxins (Dominy et al, 2004) and heavy metals (Katsumata et al, 2003). The present study aimed to investigate the role of Vit E or natural clay on growth performance, carcass traits, some blood biochemical components and Cd residues in muscles and liver of growing Japanese quail fed diets polluted by Cd at various levels.…”
Section: Introductionmentioning
confidence: 99%